EFEKTIFITAS PEMBERIAN EKSTRAK KURMA TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL TRIMESTER III DI KLINIK SUMIARIANI DAN KLINIK PRATAMA SARI TAHUN 2019 - Wulandari, Widya; siregar, yusniar; Irianti, Evi; Hasibuan, yusrawati (Poltekkes Kemenkes Medan, 2019)
Anemia is a health problem throughout the world, especially in developing countries, an estimated 30% of the world's population suffer from anemia. In Indonesia based on the results of the Basic Health Research (BHR), the prevalence of anemia in pregnant women of Indonesia in 2018 was 48.9% higher than in 2013 which was 37.1% and in 2007 of 24.5%. Dates palm are type of fruit that is rich in iron. Iron is needed in the formation of heme which can increase hemoglobin levels. This study aims to determine the effectiveness of Ajwa date palm to increase hemoglobin levels in third trimester pregnant women at the Sumiariani Clinic and Pratama Sari Clinic in 2019 This type of research was quasy experiment with one group pretest-postest approach with accidental sampling, the population is third trimester pregnant women as many as 40 respondents. Based on data collection and analysis and data is normal. The results of univariate analysis: the average change in hemoglobin levels before and after the administration of date palm extracts that is before the intervention (9.97 gr / dL) and after (10.38 gr / dL). And the results of bivariate analysis are the results of Dependent T-Test statistical test, the average hemoglobin level obtained before and after the intervention with p value = 0.00 <? = 0.05. The administration of date palm extract is effective against increasing hemoglobin levels in third trimester pregnant women at Sumiariani Clinic and Pratama Sari Clinic in 2019. For pregnant women, it can make date palm extracts together with other micronutrients such as Vitamin C to form soluble Fe complex absorption compounds that are easily dissolved, easily absorbed and made an alternative choice to increase hemoglobin levels during pregnancy.